2020
DOI: 10.1097/md.0000000000019357
|View full text |Cite
|
Sign up to set email alerts
|

Vonoprazan vs proton pump inhibitors in treating post-endoscopic submucosal dissection ulcers and preventing bleeding

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
1
12
0
2
Order By: Relevance
“…However, two systematic reviews with meta-analysis [191,192] and a network metaanalysis [193] did not find evidence of any superiority of vonoprazan over PPIs although one of these [191] highlighted a faster ulcer healing with the P-CAB. A more extensive review [194], including both RCTs and observational studies, pointed out that-while the overall ulcer healing rate did not differ between vonoprazan and PPIs-this new antisecretory compound was more effective when treating H. pylori-positive patients with ESD ulcers (Table 7). Almost all the studies evidenced a non-significant trend towards a reduced occurrence of delayed bleeding (see below).…”
Section: Vonoprazan Efficacy In the Treatment Of Peptic Ulcermentioning
confidence: 99%
See 1 more Smart Citation
“…However, two systematic reviews with meta-analysis [191,192] and a network metaanalysis [193] did not find evidence of any superiority of vonoprazan over PPIs although one of these [191] highlighted a faster ulcer healing with the P-CAB. A more extensive review [194], including both RCTs and observational studies, pointed out that-while the overall ulcer healing rate did not differ between vonoprazan and PPIs-this new antisecretory compound was more effective when treating H. pylori-positive patients with ESD ulcers (Table 7). Almost all the studies evidenced a non-significant trend towards a reduced occurrence of delayed bleeding (see below).…”
Section: Vonoprazan Efficacy In the Treatment Of Peptic Ulcermentioning
confidence: 99%
“…Factors which affected post-ESD bleeding were the type of antisecretory drug (p=0.016) and use of an antithrombotic agent (p=0.014) [215]. The benefit in prevention of delayed bleeding was not confirmed by a subsequent study [216] and by several meta-analyses [190][191][192]194] (Table 7). The equivocal results with no difference between the P-CAB, vonoprazan, and PPIs in preventing rebleeding may result from the antisecretory effects of both drugs raising pH above the pH threshold to heal and prevent rebleeding, especially after the effective coagulation of larger vessels which occurs in properly performed ESD.…”
Section: Vonoprazan Efficacy In the Treatment Of Peptic Ulcermentioning
confidence: 99%
“…This also pertains to patients receiving antithrombotic treatment. There have been six meta‐analyses of studies comparing P‐CABs with PPIs in the prevention of post‐ESD ulceration and/or bleeding 54‐59 . Pooled ulcer healing rates have been similar between vonoprazan and PPI treatment with limited evidence that delayed bleeding rates may be lower with vonoprazan.…”
Section: Vonoprazan In Peptic Ulcer Diseasementioning
confidence: 99%
“…The researchers showed that vonoprazan was more effective than PPIs for treating H. pylori-positive patients with ESD-induced gastric ulcers during the first two weeks of treatment. 27…”
Section: Management Of Gastric Ulcer Occurring After Endoscopic Submumentioning
confidence: 99%